2012
DOI: 10.1097/sla.0b013e31823fbae7
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Safety of Single-Incision Laparoscopic Colectomy

Abstract: In early series of highly selected patients, SILC appears to be feasible and safe when performed by surgeons who are highly skilled in laparoscopy. Despite technical difficulties, there may be potential benefits associated with SILC over MLC/HALC but it is yet to be proven objectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
1
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(85 citation statements)
references
References 44 publications
5
77
1
2
Order By: Relevance
“…Relatively low rates of overall morbidity and mortality were reported in the included studies, with the morbidity being 15 % and the mortality 0.75 %, a finding also supported by the meta-analysis from Makino et al [71] regarding SILC. Regarding reoperation rate, a total of nine patients were reoperated.…”
Section: Discussionsupporting
confidence: 69%
“…Relatively low rates of overall morbidity and mortality were reported in the included studies, with the morbidity being 15 % and the mortality 0.75 %, a finding also supported by the meta-analysis from Makino et al [71] regarding SILC. Regarding reoperation rate, a total of nine patients were reoperated.…”
Section: Discussionsupporting
confidence: 69%
“…In a systematic review of 23 studies with 378 patients undergoing SILC that was published in 2012, it was found that SILC carried relatively low rates of overall mortality (0.5%) and morbidity (12.9%) with operative time and estimated blood loss comparable with published data on MLC. 13 In addition, the rate of conversion to an open procedure (1.6%) in these series of SILC was significantly lower when compared with the rate of 10%-21% with MLC. These results, however, did not necessarily translate into a shorter length of stay in SILC cases compared with MLC cases.…”
Section: Single-port Partial Colectomymentioning
confidence: 99%
“…Although the use of this new approach for complex colorectal procedures might understandingly be viewed as difficult to implement, over the past few years there has been significant interest in SILS for colonic resections in both benign and malignant conditions. In fact, between 2008 and 2012, a nearly 7-fold increase occurred in the number of articles related to single-port colorectal surgery [18][19][20]. Unfortunately, the currently available literature relating to the technique includes mostly case reports or small case series describing the feasibility, safety and technical difficulties of different operations .…”
Section: Feasibility and Safety Of Single-incision Colectomymentioning
confidence: 99%